2021
DOI: 10.1016/j.fuproc.2021.106843
|View full text |Cite
|
Sign up to set email alerts
|

Torrefaction influence on combustion kinetics of Malaysian oil palm wastes

Abstract: The use of renewable energy has increased in the last decades including the consumption of biofuels, so the research focused on improving these energetic vectors has increased too, developing techniques that enhance energetic properties of these fuels. In this context, torrefaction is a thermal pre-treatment that diminishes the main disadvantages present in biomass such as hygroscopicity, low calorific value per unit mass and high susceptibility to self-ignition. In this study raw and torrefied palm oil wastes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…Kinetics mechanism provide valuable information for designing and optimizing the combustion facilities. In this study, model fitting methods of an integral method (Coats–Redfern method, CR) [ 35 , 36 , 37 ] and differential method (Freeman–Carroll, FC) [ 16 , 38 ] were employed for calculation of kinetics parameters using TGA data. The conversion rates of all reactions can be described by Arrhenius expression: where α is the conversion degree defined as ( m 0 − m t )/( m 0 − m f ); m 0 is the initial mass of the sample, g; m t is the mass of the sample at time t , g; m f is the final mass of the sample, g; E a is the apparent activation energy (kJ/mol); A is the pre-exponential factor (s −1 ); R is the universal gas constant; T is the temperature (K).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinetics mechanism provide valuable information for designing and optimizing the combustion facilities. In this study, model fitting methods of an integral method (Coats–Redfern method, CR) [ 35 , 36 , 37 ] and differential method (Freeman–Carroll, FC) [ 16 , 38 ] were employed for calculation of kinetics parameters using TGA data. The conversion rates of all reactions can be described by Arrhenius expression: where α is the conversion degree defined as ( m 0 − m t )/( m 0 − m f ); m 0 is the initial mass of the sample, g; m t is the mass of the sample at time t , g; m f is the final mass of the sample, g; E a is the apparent activation energy (kJ/mol); A is the pre-exponential factor (s −1 ); R is the universal gas constant; T is the temperature (K).…”
Section: Methodsmentioning
confidence: 99%
“…Investigation of kinetics is the fundament to reveal the combustion mechanisms and to provide references for designing industrial facilities. Thermogravimetric analysis (TGA) has been proved to be an effective method to understand the combustion mechanism of solid fuels [ 16 ]. Ignition temperature ( T i ), burnout temperature ( T p ) etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model-fitting method such as the Coats-Redfern method is utilised as well with the added benefit of being able to hypothesize reaction mechanisms for the process. For example, Castells et al (2021) presented a preliminary view that empty fruits bunch (EFB) samples showed a better fit for the diffusion reactions, while oil palm shell (OPS) and palm mesocarp fibre (PMF) could better fit n-order reactions under a combustion scheme. Surahmanto et al (2020) applied the Coats-Redfern integral method for kinetic analysis of oil palm waste and found that they are best fitted to first-order reactions in the pyrolysis scheme.…”
Section: P R E S Smentioning
confidence: 99%
“…The second most important factor is the legal regulations related to environmental protection [3]. One of the renewable energy sources are biofuels produced from biomass [4,5]. Depending on the physical state of the final product, it is possible to distinguish solid [6,7], liquid [8], and gaseous biofuels [9,10].…”
Section: Introductionmentioning
confidence: 99%